Creation, catastrophe, and calvary : Why a global flood is vital to the doctrine of atonement - Baldwin, John Templeton (Review and Herald Publishing Association, 2000)
"In this scientific age, what difference does it make whether I believe the world was created in six literal days and that the world was destroyed by a global flood?" In answering these questions, Creation, Catastrophe, and Calvary shows how these beliefs are related to key issues such as the forgiveness of our sins and Sabbath observance.